PENERAPAN BUDAYA ORGANISASI (STUDI KASUS PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK CABANG DAGO BANDUNG) - Arcaya Yudha; Herbasuki Nurcahyanto; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
BRI Branch Dago Office is the only one that has a priority service functions branch office in Bandung that operate under the supervision of the Office of the BRI Bandung. Branch office is a BRI branch office that implement functions to raise funds from the public in the form of savings and channel them to the public in the form of credit and or other forms in order to improve the living standard of the people, which is responsible to the Regional Office. This study aims to identify and analyze models of organizational culture and the implementation of organizational culture values in PT. Bank Rakyat Indonesia branch Dago Bandung so as to know what needs to be repaired and maintained. Model of organizational culture and the implementation of the cultural values of the organization are identified and analyzed from the organizational structure, human resource management policies, integrity, professionalism, customer satisfaction, exemplary and respect for human resource. In this study, researchers used a purposive technique. Data collection method used is in-depth interviews and documentation techniques. This study shows that the model of organizational culture and the implementation of organizational culture values indicate there is still a problem in terms of integrity and professionalism, integrity is still considered less value because of the work period is too short for contract workers, so that the organizational culture is not well understood by contract workers who are at the forefront of service. professionalism that most of the cutting edge services are contract workers who were given a short training, a result is they lack an understanding of the products of the Bank Rakyat Indonesia branch Dago